Enhancing student learning outcomes on cultural diversity through the cooperative learning model ‘Make a Match’ - Nuzulia Putri; Meriza Faradilla; Khairul Rizal (International Journal of Advances in Educational Research, 2024)
This study aims to improve fifth-grade students' learning outcomes on cultural diversity using the cooperative learning model "Make a Match." Conducted as Classroom Action Research (CAR) over two cycles, the study involved observation, reflection, planning, and implementation stages. The research was conducted at an elementary school with 25 fifth-grade students as participants. Data collection tools included learning outcome tests, observation sheets, and documentation. The results showed that the "Make a Match" model significantly enhanced student learning. In the first cycle, the average learning outcome was 72.4, with a classical completeness percentage of 68%. In the second cycle, the average increased to 85.6, with a classical completeness percentage of 92%. Moreover, student engagement in learning activities improved significantly. Thus, the "Make a Match" cooperative learning model effectively enhanced fifth-grade students' learning outcomes on cultural diversity. Teachers are encouraged to adopt this model as an alternative teaching strategy for other subjects.